Synthesis of Some ’N’ Bridgehead Heterocycles Containing Quinoxaline and 1,2,4-Triazole and Their Antifungal and Antitubercular Activity - RAMALINGAM, P.; BABURAO, CH.; GANAPATY, S. (Asian Journal of Chemistry, 2010)
2,3-Dichloroquinoxaline reacted with 5-substituted 3,4- diaminotriazole afforded 3-substituted quinoxalino(2,1b)- 1,2,4-triazolo(5,1c) 5-substituted-1,2,4-triazole. The structures were supported by spectral studies and evaluated for their antifungal and antitubercular activities.